Back to the future: Extended dialysis for treatment of acute kidney injury in the intensive care unit - Kielstein, Jan T.; Schiffer, Mario; Hafer, Carsten (Journal of Nephrology, 2010)
On September 11, 1945, Maria Schafstaat was the first patient who successfully underwent a dialysis treatment for acute kidney injury (AKI). The ingenious design of the first dialysis machine, made of cellophane tubing wrapped around a cylinder that rotated in a bath of fluid, together with the brave determination to treat patients with AKI, enabled the Dutch physician W.J. Kolff to save the life of the 67-year-old woman. By treating her for 690 minutes (i.e., 11.5 hours) with a blood flow rate of 116 ml/min, Kolff also set the coordinates of a renal replacement therapy that has enjoyed an unsurpassed renaissance over the last decade for treatment of severely ill patients with AKI in the intensive care unit (ICU). Prolonged dialysis time with low flow rates - these days, called extended dialysis (ED) - combines several advantages of both intermittent and continuous techniques, which makes it an ideal treatment method for ICU patients with AKI. This review summarizes our knowledge of this method, which is increasingly used in many centers worldwide. We reflect on prospective controlled studies in critically ill patients that have documented that small-solute clearance with ED is comparable with that of intermittent hemodialysis and continuous venovenous hemofiltration, as well as on studies showing that patients' cardiovascular stability during ED is similar to that with continuous renal replacement therapy. Furthermore, we report on logistic and economic advantages of this method. We share our view on how extended dialysis offers ample opportunity for a collaborative interaction between nephrologists and intensivists as the nephrology staff, enabling optimal treatment of complex critically ill patients by using the skill and knowledge of 2 indispensable specialties in the ICU. Lastly, we address the problem of ED intensity, which does not seem to have an impact on survival at higher doses, a finding that might be caused by the fact that we still adhere to dosing guidelines for antibiotics which are at best ineffectual but might also lead to potentially dangerous underdosing of these life-saving drugs. © 2010 Società Italiana di Nefrologia.
CRIS-Team Scopus Importer:2020-11-12
Keywords: Acute kidney injury; Continuous renal replacement therapy; Extended dialysis; Intensive care unit; Intermittent hemodialysis